Supramolecular Arrangement in Styphnic Acid and Naphthalene-1,4-diol (1 : 1) through a Novel Synthetic Rote for Styphnic Acid - Moamen S. Refat; Hossam A. Saad; Mohamed Y. El-Sayed; Abdel Majid A. Adam; Okan Zafer Yeşilel; Murat Taş (Journal of Chemistry)
The chemical preparation and crystal structure of styphnic acid and naphthalene-1,4-diol (1 : 1) (I) have been reported. The compound crystallizes in the orthorhombic system in space group Pnma and cell parameters a=6.6712(2), b=16.8267(7), c=13.6450(5) Å and V=1531.71(10) Å3, and Z=4. Crystal structure has been determined and refined to R=0.0576. The crystal structure of I, the asymmetric unit, contains C6H2N3O7, C10H7O, and it is a half portion of both styphnic acid and naphthalene-1,4-diol. The O1–H1⋯O2 intramolecular hydrogen bond was found between the O–H and a nitro group in the styphnic acid unit.